Capacity strengthening of animal genetic improvement education in Africa - Aggrey, S.E.; Osei-Amponsah, R.; Kugonza, D.R.; Mrode, Raphael A.; Rekaya, R.; Rege, J.E.O. (Springer, 2025)
Africa is home to a rich diversity of farm animal genetic resources which play major roles in poverty alleviation, food, and nutritional security as well as helping meet various socio-cultural needs. These valuable animal resources range from the major species such as pigs, cattle, sheep, goats, donkeys, camelids, poultry, aquatic resources, and bees to micro-livestock such as guinea fowl, grasscutters, and cavies. In line with the Global Plan of Action on Animal Genetic Resources, there is a need for Africa to sustainably manage these resources and help ensure their conservation. Genetic improvement of Africa’s animal resources will be key to breeding resilient, productive, and climate-adaptive animals for the current and future generations. Unfortunately, Africa continues to lag behind in both the institutional and human resource capacity for animal genetic resources management, including improvement. This chapter presents a brief overview of human resources capacity challenges, limitations in animal breeding and genetics and subsequently suggests how to turn some of the challenges into opportunities. The basic concepts and misconceptions in animal breeding, lessons learned from past capacity-building initiatives, and the need to improve agricultural education in primary and secondary schools are covered. Additionally, we review post-secondary technical education and graduate education in animal breeding. Finally, we highlight the need to embrace good collaborative partnerships to enable Africa to boost its human and institutional capacity in order to take advantage of current and emerging innovative technologies in animal breeding education.